Goal Orientations, Self-Regulated Learning Strategies and Problem-Solving: A Mediational Analysis. - Bibi, Aisha; Ahmad, Mushtaq (Pertanika Journal of Social Sciences & Humanities, 2022)
This study investigates goal orientations, and self-regulated learning (SRL) strategies, particularly for differential equations (DEs) based problem-solving. Two adapted selfdesigned questionnaires for goal orientations, and SRL and an assessment test containing five self-developed DEs tasks were distributed among 430 students studying in intercolleges. Collected data was further examined through SPSS and Smart PLS software. Initially, direct effects of goal orientations (mastery, performance, and avoidance goal) and SRL (elaboration and critical thinking) were considered. Findings revealed that mastery, avoidance goals, and elaboration had a significant direct effect on DEs' problem-solving. However, no such effect was observed for performance goals and critical thinking. Similarly, it was revealed that only elaboration had the role of mediation for both mastery and performance goals. Likewise, in the case of critical thinking, no significant effects were observed. The current study confirmed that goal orientations and SRL strategies influence DE problem-solving. Therefore, educators and teachers may structure their classroom activities to review and incorporate these learning strategies, which will enhance students' internal motivation, resulting in significant improvement in their problemsolving ability.